The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1300/j084v13n04_01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a Volunteer Ombudsman Program: The Rhode Island Experience

Abstract: The research assessed the impact of a major innovation in the Long-Term Care Ombudsman Program that occurred in Rhode Island in 1997-the introduction of a volunteer component in which community members were trained and certified as advocates for residents in long-term care. Based on reports to the state ombudsman office, the findings indicated that the placement of volunteer ombudsman was associated with the generation of more complaints and more serious complaints about the facilities in which they were place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Details of individual studies are reported in Table 1. Fourteen quantitative or mixed methods studies evaluated the impact of volunteering (Baker et al., 2017; Caspar et al., 2019; Clarkson et al., 2007; Di Bona et al., 2019; Lee et al., 2007; Lokon et al., 2017; Low et al., 2015; McNair & Moore, 2010; Sauer et al., 2016; Seitz et al., 2016; Skropeta et al., 2014; van Zon et al., 2016; Westerhof et al., 2018; Xaverius & Mathews, 2004), and 22 reported questionnaire or qualitative data (Biggs & Knox, 2014; Bradley et al., 2000; Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Hill, 2016; Hunter et al., 2018; Jain et al., 2020; Kawamura et al., 2009; Keith, 2001; Keith & Schafer, 2002; Landau et al., 2013; Lokon et al., 2012; Ostwald et al., 2003; Persson, 2004; Santini et al., 2018; Schwalbach & Kiernan, 2002; Somers, 2018; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012, 2014). Overall the quality of studies is poor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of individual studies are reported in Table 1. Fourteen quantitative or mixed methods studies evaluated the impact of volunteering (Baker et al., 2017; Caspar et al., 2019; Clarkson et al., 2007; Di Bona et al., 2019; Lee et al., 2007; Lokon et al., 2017; Low et al., 2015; McNair & Moore, 2010; Sauer et al., 2016; Seitz et al., 2016; Skropeta et al., 2014; van Zon et al., 2016; Westerhof et al., 2018; Xaverius & Mathews, 2004), and 22 reported questionnaire or qualitative data (Biggs & Knox, 2014; Bradley et al., 2000; Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Hill, 2016; Hunter et al., 2018; Jain et al., 2020; Kawamura et al., 2009; Keith, 2001; Keith & Schafer, 2002; Landau et al., 2013; Lokon et al., 2012; Ostwald et al., 2003; Persson, 2004; Santini et al., 2018; Schwalbach & Kiernan, 2002; Somers, 2018; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012, 2014). Overall the quality of studies is poor.…”
Section: Resultsmentioning
confidence: 99%
“…Nine papers discussed volunteer motivations for their involvement with care homes and care home residents (Damianakis & Wagner, 2007; Filinson, 2003; Gundersen & Johannessen, 2018; Keith, 2003; Lokon et al., 2012; Ostwald et al., 2003; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012). These included a desire to help others or “give something back” (Damianakis & Wagner, 2007; Gundersen & Johannessen, 2018; Keith, 2003; Ostwald et al., 2003; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012); providing the volunteer with a sense of purpose (Damianakis & Wagner, 2007; Filinson, 2003; Van der Ploeg et al., 2012); utilising personal and professional experiences (Damianakis & Wagner, 2007; Keith, 2003; Tanner & Brett, 2014; Van der Ploeg et al., 2012) and using volunteer opportunities to enhance career prospects (Lokon et al., 2012; Tanner & Brett, 2014; Tinker et al., 2017; Van der Ploeg et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations